Hyaluronan production and chondrogenic properties of primary human chondrocyte on gelatin based hematostatic spongostan scaffold - Klangjorhor J. (BioMed Central, 2015)
Background: Autologous chondrocyte transplantation is a promising technique for treatment of cartilage defects. Three dimensional chondrocyte cultures on a scaffold are widely used to retain the chondrogenic phenotype. Using a biodegradable gelatin scaffold is one option for the cell delivery system, but molecular and histological studies of the method have not yet been done.Methods: We evaluated the chondrogenic property of the primary human chondrocyte on a gelatin scaffold as compared to a collagen scaffold over a period of 21 days. We examined the production of glycosaminoglycan by quantitative and histological analysis. Gene expression of cartilage-associated molecules was assessed by quantitative RT-PCR.Results: The gelatin scaffold showed the ability to promote chondrocyte expansion, chondrogenic phenotype retention at molecular and mRNA levels.Conclusions: This scaffold is thus suitable for use as an in vitro model for chondrocyte 3D culture. © 2012 Klangjorhor et al.; licensee BioMed Central Ltd.